DOI: 10.31274/rtd-180813-12843
|View full text |Cite
|
Sign up to set email alerts
|

The association of administrators' learning styles, background differences, and teacher appraisal judgments

Abstract: CHAPTER 1. INTRODUCTION No longer is the matter of teacher performance evaluation a question of whether or not it should be done. The question now is how best to evaluate teacher performance and what should be evaluated (6, 7, 78, 108). All teachers are evaluated. Regardless of how formal the evaluation system is, what evidence is collected and analyzed, or how often formal reports are written, teachers are evaluated and evaluated often. They are evaluated by students, parents, other teachers, administrators, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
4
0

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 41 publications
2
4
0
Order By: Relevance
“…However, for male evaluators a similar trend was found, with higher mean ratings given to female teachers (4.02) than to male teachers (3.89). These findings are similar to those of Harrington (1984) but dissimilar to results obtained by Landy and Farr (1983). Both of these research efforts, however, were conducted In laboratory settings using simulated samples of employee work performance.…”
Section: Discussionsupporting
confidence: 71%
See 1 more Smart Citation
“…However, for male evaluators a similar trend was found, with higher mean ratings given to female teachers (4.02) than to male teachers (3.89). These findings are similar to those of Harrington (1984) but dissimilar to results obtained by Landy and Farr (1983). Both of these research efforts, however, were conducted In laboratory settings using simulated samples of employee work performance.…”
Section: Discussionsupporting
confidence: 71%
“…The only trend noted among some of those studies was a tendency for female raters to assign more lenient ratings than their male counterparts, a tendency noted also by Carroll (1982). Harrington (1984), on the other hand, found that females gave lower ratings than male evaluators when assessing the performance level of a teacher's video-taped lesson.…”
Section: Rater Characteristicsmentioning
confidence: 97%
“…Standards have long been a topic of study. At least six Iowa State University researchers sought to contribute knowledge in this area (Cameron, 1973;Garcia, 1980;Rucker, 1981;Westerberg, 1983;Harrington, 1984;and Peterson, 1988). How one monitors and reports progress has been the topic of another group of researchers (Edwards, 1985;Semones, 1987;Stevenson, 1987;Floden, 1987;and Wicks, 1988).…”
Section: Historical Considerationsmentioning
confidence: 99%
“…In more recent studies of the relationship between gender and performance evaluation in the educational setting, gender was concluded to be a main effect. Females were found to be tougher raters than males (Harrington, 1984;Peterson, 1988).…”
Section: Leniency/severitymentioning
confidence: 91%
“…In a study conducted in 1960, D. G. Ryans attempted to show a correlation between predicted teacher performance and summative effectiveness rating. Recent studies conducted at Iowa State University (Harrington, 1984;Bourisaw, 1988;and Peterson, 1988) have concluded that biases do influence the rating of teacher performance.…”
Section: Statement Of the Problemmentioning
confidence: 99%